Adverse childhood experiences and unhealthy dietary behaviours in adulthood - Alexander Testa; Lixia Zhang; Dylan B Jackson; Kyle T Ganson; Julia H Raney; Jason M Nagata (Cambridge University Press, 2024)
Abstract Objective: This study assesses the relationship between adverse childhood experiences (ACE) occurring before the age of 18 years and patterns of fast-food consumption and sugary beverage consumption in adulthood. The study also examines how perceived stress and socio-economic status (SES) (college educational attainment and income) in adulthood mediate this relationship. Design: Using data from the National Longitudinal Study of Adolescent to Adulthood Health (N 8599), multinomial logistic regression analyses were carried out to assess the association between ACE and unhealthy dietary behaviours in adulthood. Karlson-Holm-Breen mediation analysis is used to determine the mediating effects of SES and perceived stress. Setting: Persons living in the USA in 2016-2018. Participants: Adults (n 8599) aged 33-44 years. Results: The findings show an association between four or more ACE and high fast-food (relative risk ratio (RRR) = 1·436, 95 % CI = 1·040, 1·983) and high sugary beverage consumption (RRR = 1·435, 95 % CI = 1·002, 2·055). The association between ACE and high fast-food consumption is partially mediated by college educational attainment, and the association between ACE and high sugary beverage consumption is partially mediated by perceived stress and college educational attainment. Conclusions: ACE can have long-term consequences for unhealthy dietary behaviours in adulthood, and this relationship is partially due to a lower likelihood of higher perceived stress and college educational attainment among ACE-exposed persons. Future research is needed to understand further the influence of ACE on dietary patterns over the life course.